Financial transfers between Poland and the European Union within Common Agricultural Policy against the background of the New Member States' experiences after 2004 - Czyżewski, Andrzej; Poczta-Wajda, Agnieszka; Sapa, Agnieszka (Transfery finansowe między Polską a Unią Europejską w ramach Wspólnej Polityki Rolnej na tle nowych krajów członkowskich po roku 2004, 2011)
Since Poland has already been a member of the European Union for over six years, it is proper time to look closer at the benefits which participation in the Common Agricultural Policy brought to the Polish agricultural sector. The main aim of the paper is to present the value and dynamics of financial transfers between Poland and the EU within the CAP in 2004-2009 against the background of the countries which joined the EU after 2004. The analysis, which includes both transfers from the EU as well as the expenditure from national budget for the pre-financing of the CAP, proves that Polish agricultural sector is a net beneficiary of the Polish integration with the EU and plays a key role in the economic policy of the EU towards Poland
Ekonomia = Economics, 2011, Nr 2 (14), s. 123-131
Keywords: Common Agricultural Policy; agricultural sector; budgetary expenditure